Determination of the safe crack length and cohesive traction distribution using the model of a crack with prefacture zone - Selivanov, M. F. (Reports of the National Academy of Sciences of Ukraine, 2014)
The loaded at infinity plate with a central mode I crack is considered. Using the cohesive zone model, a solution for crack displacements is given. Constitutive relationships for the safe crack length corresponding to the cohesive zone length and parameters of a cohesive traction distribution are found for the given intensity of an external load. Numerical solutions are obtained for tractionseparation relationships such that the cohesive traction at the cohesive crack tip exceeds the external load intensity.